2001
DOI: 10.1002/esp.227
|View full text |Cite
|
Sign up to set email alerts
|

Experimental frost weathering of sandstone by various combinations of salts

Abstract: Weathering experiments are reported combining frost and a range of salts that occur naturally on rock faces in western and central Europe. Potassium and ammonium alums enhanced frost weathering quite considerably, both singly and in combination, though they were less potent than halite, the destructiveness of which, at sub-zero temperatures, was again confirmed. By contrast, alunogen and gypsum had little or no effect on rates of frost weathering either singly or in combination. Combining halite and gypsum pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 12 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…More recent experimental designs have made some progress toward simulating salt-rich environments with a greater degree of fidelity, through the application of salt solutions of low concentrations (e.g., Goudie, 1993;Warke and Smith, 1994), or through the application of salt mixtures (e.g., Jerwood et al, 1990a,b). Combinations of salts have not been widely used Williams and Robinson, 2001); further investigation is required to elucidate the combined effects of salts in causing damage. Steiger and Zeunert (1996) suggested that it is virtually impossible to predict the behavior of a salt mixture from the properties of the pure components; however, chemical models of behavior of salt mixtures over ranges of temperatures and humidities may extend our understanding of the properties of salt systems in sandstone (e.g., Price, 2000).…”
Section: Reductionism and Weathering Studiesmentioning
confidence: 99%
“…More recent experimental designs have made some progress toward simulating salt-rich environments with a greater degree of fidelity, through the application of salt solutions of low concentrations (e.g., Goudie, 1993;Warke and Smith, 1994), or through the application of salt mixtures (e.g., Jerwood et al, 1990a,b). Combinations of salts have not been widely used Williams and Robinson, 2001); further investigation is required to elucidate the combined effects of salts in causing damage. Steiger and Zeunert (1996) suggested that it is virtually impossible to predict the behavior of a salt mixture from the properties of the pure components; however, chemical models of behavior of salt mixtures over ranges of temperatures and humidities may extend our understanding of the properties of salt systems in sandstone (e.g., Price, 2000).…”
Section: Reductionism and Weathering Studiesmentioning
confidence: 99%
“…Most probably this was due to the low concentration of the prepared salt solution as well as a relatively high freezing temperature. As emphasized by Williams and Robinson [11], the effectiveness of different salts depends not only on the concentration and type of salt, but also on the intensity of the freeze-thaw regime [4], [5]. However, this process leads to a decrease of uniaxial compressive strength in relation to the strength of these rocks in the air-dry state, as evidenced by the values of the coefficients of resistance to the action of de-icing salt (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately the migration of the de-icing salt to the neighboring buildings causes the accumulation of chloride on their near ground level and the subsequent resulting deterioration [9]. Most of the laboratory studies deal with the role of de-icing salts in the frost damage and emphasize their high harmfulness to the structure of stones [1], [2], [10], [11], although there are some that describe their positive action. McGreevy [7], for example, using more dilute solutions, found that salts could actually inhibit frost weathering under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In rainy conditions, however, something else occurred. Perhaps hydration effects took place, re-hydrating algal biofilm, or deposited salt crystals from retreating ocean or salt spray were dissolved (Williams and Robinson, 2001), in turn concealing the effect of rock surface cooling or heating. But why are differences in rock behaviour between summer and winter sampling periods observed?…”
Section: Discussionmentioning
confidence: 99%